PENGARUH IKLAN DAN CITRA MEREK TERHADAP MINAT BELI PRODUK KOSMETIK SOMETHINC (Studi Kasus Pada Mahasiswa FEB Universitas Islam Assyafiiyah) - C Chusnah; S Sunarno; Badriyatun Nurul Khopipah (El-Arbah: Jurnal Ekonomi, Bisnis Dan Perbankan Syariah, 2024)
This research aims to obtain empirical evidence regarding the influence of advertising and brand image on interest in purchasing Somethinc cosmetic products among FEB UIA students. Data was obtained from 100 students through questionnaires and analyzed using multiple regression, multiple correlation, and t and f hypothesis tests. The results of the analysis show that there is a positive and significant influence between advertising (X1) and brand image (X2) on purchasing interest (Y), with t- values of 14.092 and 13.733 respectively which exceed ttable 1.661. The Ftest of 127.681 exceeds the Ftable of 3.09, resulting in approval of Ho and acceptance of Ha, indicating the significant influence of advertising and brand image on purchasing interest. The coefficient of determination shows that the contribution of advertising and brand image is 72.5%, while other factors not explained in the research contribute 27.5%.